"The constipation conundrum": Improving recognition of constipation on a gastroenterology ward. Issue 1 (3rd October 2016) - Jackson, Robert; Cheng, Philip; Moreman, Sarah; Davey, Nicola; Owen, Lisa
Abstract : Constipation is a common and often overlooked problem, but it can cause serious complications for patients including pain, nausea, urinary retention, and prolonged hospital admission. There are no recognised criteria for the diagnosis of constipation in the acute hospital setting, and it is often the role of the ward doctor to identify and manage this problem. Completion and monitoring of "stool charts" by nursing and medical staff is key to proper recognition and management of constipation. A baseline study found that while charts were completed well, they were only monitored by doctors 17.5% of the time. This quality improvement project introduced an altered "continuation sheet" to the clinical notes to prompt monitoring of stool charts and provide an area for documentation. This resulted in an increase in monitoring to 66.7%.